CHITOSAN ISOLATION AND ITS APPLICATION TO REDUCE THE CONTENT OF METAL IONS IN WELLBORE WATER - Amri, Yulida; Fajri, Rahmatul; Batu, Matius Stefanus (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2019)
Potential water sources such as white shrimp shell waste (Penaeus merguiensis) can be used as a source of chitosan. Chitosan can be applied as an environmentally friendly adsorbent for water treatment because of its ability to adsorb metal ions. In this study, chitosan was isolated through several stages such as demineralization, deproteination, decolourization and deacetylation. The yield of chitosan obtained from this study was 17.73%. Characterization by infrared spectroscopy (FTIR) showed the absorption at 3355 cm-1 indicating the presence of amine (-NH2) and hydroxyl (-OH) groups. The absorption of the carbonyl group (-C=O) at 1642 cm-1 disappeared while the absorption of the free amine group (-NH2) at 1590 cm-1 increased indicating the successful deacetylation with a degree of deacetylation (DD) 78%. Application of chitosan in wellbore water did not affect on colour change and decreasing of iron (Fe) content due to low concentration of iron (Fe). However, chitosan can reduce the pH value of water and manganese (Mn) content. The results of ANOVA and DMRT test at 0.05 significance level showed that chitosan with various mass had different effects. The more the mass of chitosan added, the higher the content of manganese (Mn) will decrease.